Molecular deficits relevant to concussion are prevalent in top-ranked football players entering the National Football League Draft - Kunces, L. J.; Keenan, J.; Schmidt, C. M.; Schmidt, M. A. (The Journal of Strength and Conditioning Research, 2021)
Characterization of blood variants in athletes entering the highly competitive contact environment of professional football can help us understand the risk for brain injury. When coupled with longitudinal follow-up of future concussion incidence and trajectory, it may provide additional insight into factors that influence brain injury. We observed the metabolic phenotype of collegiate football players entering the 2016 National Football League (NFL) draft. The principal aims were to characterize the molecular status of individual athletes and quantify the prevalence of athletes with multiple concurrent molecular deficits. Blood was taken from 30 elite American collegiate football players 7 weeks before the NFL scouting combine and 15 weeks before entering the NFL draft. Average results revealed suboptimal values in Omega-3 Index (avg ± std, 4.66 ± 1.16%), arachidonic acid:eicosapentaenoic acid fatty acid ratio (29.13 ± 10.78), homocysteine (11.4 ± 3.4 µmol/L), vitamin D (30 ± 11.4 ng/ml), and red blood cell magnesium (4.1 ± 0.8 mg/dl). Using sport-optimized reference ranges from previously published research, 10% presented with 3, 40% presented with 4, and 50% of athletes presented with 5 suboptimal values at once. We conclude molecular deficits in this cohort entering the NFL draft were common, with a significant number of athletes presenting with multiple suboptimal levels. The significant commonality of the suboptimal biomarkers is relevance to brain health and function. This data warrant extensive metabolic phenotyping and consideration of prophylactic precision nutrition countermeasures by the multidisciplinary staff for athletes entering contact environments.